«Indissolubile vinculum karitatis». Pier Damiani e Alfano I di Salerno - Antonio Sordillo (E-theca OnLineOpenAccess Edizioni, 2021)
The epistle 49 by Peter Damian contains an original allegorical interpretation of the Jewish Sabbath as a day of rest, enriched by a mystical exegesis of the biblical Hexameron, in which the six days of creation correspond to the inner journey of man called to intimately unite with God. Peter Damian expresses this process of deification through the two images of man as microcosm and sovereign of creation and man as temple of God. The main source of Damian’s text seems to be the De natura hominis by Nemesius of Emesa, which he knows thanks to the translation of Alfanus I of Salerno, one of the recipients of the epistle: this is confirmed by textual evidences, but also by a preliminary historical and historiographic reconstruction of the clue of friendship that binds Peter Damian to the archbishop of Salerno.